2019
DOI: 10.3748/wjg.v25.i25.3108
|View full text |Cite
|
Sign up to set email alerts
|

Advanced imaging in surveillance of Barrett’s esophagus: Is the juice worth the squeeze?

Abstract: Esophageal cancer is on the rise. The known precursor lesion is Barrett’s esophagus (BE). Patients with dysplasia are at higher risk of developing esophageal cancer. Currently the gold standard for surveillance endoscopy involves taking targeted biopsies of abnormal areas as well as random biopsies every 1-2 cm of the length of the Barrett’s. Unfortunately studies have shown that this surveillance can miss dysplasia and cancer. Advanced imaging technologies have been developed that may help detect dysplasia in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Endoscopy can detect esophageal cancer, even those at an early stage [ 25 ]. Using a combination of high-definition white light, narrow band imaging, and both targeted and random biopsy, endoscopy can detect mucosal abnormalities that indicate preneoplastic or neoplastic conditions of the esophagus [ 26 , 27 , 28 , 29 ]. These findings can include nodularity, altered pit pattern or vascularity, depression, and protruding lesions, with upper endoscopy being recommended for esophageal cancer surveillance for individuals at high risk [ 30 ].…”
Section: Esophageal Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopy can detect esophageal cancer, even those at an early stage [ 25 ]. Using a combination of high-definition white light, narrow band imaging, and both targeted and random biopsy, endoscopy can detect mucosal abnormalities that indicate preneoplastic or neoplastic conditions of the esophagus [ 26 , 27 , 28 , 29 ]. These findings can include nodularity, altered pit pattern or vascularity, depression, and protruding lesions, with upper endoscopy being recommended for esophageal cancer surveillance for individuals at high risk [ 30 ].…”
Section: Esophageal Cancermentioning
confidence: 99%
“…These findings can include nodularity, altered pit pattern or vascularity, depression, and protruding lesions, with upper endoscopy being recommended for esophageal cancer surveillance for individuals at high risk [ 30 ]. Accordingly, there are guidelines for screening of esophageal cancer in those at high risk, which in western countries focus primarily on surveilling for lesions associated with Barrett’s esophagus [ 26 , 27 , 28 , 29 ].…”
Section: Esophageal Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…To date, numerous microbiome surveys have been conducted to identify the gut microbiome profile in IBD, especially focusing on the differences between the profile of IBD patients and that of healthy controls. Compelling studies in animal models and humans have provided evidence of persistent imbalance on the gut microbiome in IBD [ 29 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ]. However, it remains to be determined whether these changes in the microbiome are the cause of IBD or rather the result of inflammation after IBD onset.…”
Section: Gut Dysbiosis In Inflammatory Bowel Diseasementioning
confidence: 99%
“…Studies have shown that the risk of esophageal cancer in patients with Barrett esophagus is 30 -120 times the risk in ordinary people (1,2). Therefore, it is of great significance to properly understand the risk factors of the transformation of Barrett esophagus into esophageal carcinoma to reduce the incidence of malignant tumors (3).…”
Section: Introductionmentioning
confidence: 99%